On the Eightieth Birthday of Sergei Nikolaevich Bagayev. (October 2021) - Sergeev, A M; Balega, Yu Yu; Andreev, A F; Garanin, S G; Zabrodskii, A G; Zelenyi, L M; Krokhin, O N; Kulchin, Yu N; Konov, V I; Litvak, A G; Mesyats, G A; Rubakov, V A; et al.
Abstract: Academician Sergei Nikolaevich Bagayev, an eminent physicist and science organiser, director of sciences at the Institute of Laser Physics (ILP), Siberian Branch (SB), Russian Academy of Sciences (RAS), was 80 on 9 September 2021.